Studi pemanfaatan pupuk abu boiler pada pertumbuhan bibit tanaman kakao (Theobroma cacao L.) - Yulius Gae Lada (Jurnal Agercolere, 2019)
Boiler ash is a solid waste from biomass combustion from palm oil mills. The boiler ash can be used as fertilizer because it has a high content in the samples of N, P, K and Mg and is safe for the environment. This study aims to determine the effect of boiler ash fertilizer on the growth of cocoa seedlings and get the optimal fertilizer dose when applied. This research was conducted in Jayapura – Papua for 3 months (September – November). This study used a completely randomized design that was repeated as many as 6 replications. The treatments given include: A0 (control), A1 (300 g.polybag–1), A2 (350 g.polybag–1), A3 (400 g.polybag–1) and A4 (450 g.polybag–1). Parameters measured were plant height, leaf number, leaf width, leaf length and plant wet weight. Based on statistical tests, the results showed that the use of boiler ash fertilizer on the growth of cocoa seedlings which was seen from all parameters had no significant effect. However, A4 treatment using 450 g of boiler ash fertilizer per polybag gives significant results for all parameters measured.